Impacts of COVID-19 Pandemic on Gastrointestinal Endoscopy Volume and Diagnosis of Gastric and Colorectal Cancers: A Population-based Study (2020)
The coronavirus disease (COVID-19) pandemic has caused a major disruption to our healthcare system. In response to the service demand surge and shortage of personal protective equipment, multiple professional societies have issued recommendation to defer elective endoscopic procedures, except time-sensitive and emergency procedures.1-3 As yet, the real-life impact of this pragmatic service reduction is unknown. Herein, we reported the short-term impacts of the COVID-19 pandemic on the volume of gastrointestinal endoscopy and new diagnosis of gastric and colon cancers in Hong Kong, and modelled on the changes in cancer staging.